1999
DOI: 10.21273/jashs.124.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pod Calcium Concentration between Two Snap Bean Populations

Abstract: To understand the genetics that control pod Ca concentration in snap beans, two snap bean (Phaseolus vulgaris L.) populations consisting of 60 genotypes, plus 4 commercial cultivars used as checks, were evaluated during Summers 1995 and 1996 at Hancock, Wis. These populations were CA2 (`Evergreen' × `Top Crop') and CA3 (`Evergreen' × `Slimgreen'). The experimental design was an 8×8 double lattice repeated each year. No Ca was added to the plants grown in a sandy loam soil wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…With higher ET, more water moves through the plant and since Ca moves with the transpiration stream, more Ca moves into the plant and fruit. Quintana et al (1999) suggested differences in bean Ca concentration from year to year were due to variations in rainfall, temperature, and other environmental factors. In the study, beans that had higher Ca concentrations were grown during the season that was higher in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…With higher ET, more water moves through the plant and since Ca moves with the transpiration stream, more Ca moves into the plant and fruit. Quintana et al (1999) suggested differences in bean Ca concentration from year to year were due to variations in rainfall, temperature, and other environmental factors. In the study, beans that had higher Ca concentrations were grown during the season that was higher in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Results from this study indicate that efforts to improve Ca and Mg concentration of broccoli through genetic improvement may be impeded by the significant influence that the environment can have on ultimate concentrations, and also by potential negative linkages between mineral concentration and other traits such as head weight. In a recent paper, Quintana et al (1999) concluded that environmental effects should not hinder breeding efforts to enhance Ca content of snap bean. That conclusion for snap bean, differs from our prediction for broccoli, emphasizing that efforts to enhance mineral concentration must be examined on a crop by crop basis.…”
Section: Discussionmentioning
confidence: 99%